Use of pyocin to select a Haemophilus ducreyi variant defective in lipooligosaccharide biosynthesis. - Campagnari, A A (1994)
Haemophilus ducreyi, a cause of genital ulcer disease in developing countries, appears to facilitate the heterosexual transmission of the human immunodeficiency virus in Africa. Despite an increase in studies of this gram-negative human pathogen, little is known about the pathogenesis of chancroid. Our studies have shown that the lipooligosaccharides (LOS) of H. ducreyi may play an important role in ulcer formation. Monoclonal antibody and mass spectrometric analyses identified a terminal trisaccharide present on H. ducreyi LOS that is immunochemically similar to human paragloboside. This epitope is present on the LOS of Neisseria gonorrhoeae, and it may be the site of attachment for pyocin lysis. We have used pyocin, produced by Pseudomonas aeruginosa, to select LOS variants with sequential saccharide deletions from N. gonorrhoeae. On the basis of the similarities between N. gonorrhoeae and H. ducreyi LOS, we employed the same technique to determine if H. ducreyi strains were susceptible to pyocin lysis. In this study, we report the generation of a pyocin N-resistant H. ducreyi strain which synthesizes a truncated version of the parental LOS. Further studies have shown that this H. ducreyi variant has lost the terminal LOS epitope defined by monoclonal antibody 3F11. This report demonstrates that H. ducreyi is sensitive to pyocins and that this technique can be used to generate H. ducreyi LOS variants. Such variants could be used in comparative studies to relate LOS structure to biologic function in the pathogenesis of chancroid.